Analysis of good distribution practice inspection deficiency data of pharmaceutical wholesalers in Bulgaria - Assena Stoimenova; Bogdan Kirilov; Krassimira Zaykova (Pensoft Publishers, 2019)
The current study analyses the regulatory inspection findings of the wholesalers in Bulgaria in 2017 and compares the results with the findings from some other EU member-states. In total, 48 GDP inspections were performed in 2017. 50% of the inspections were performed in relation with issuing an authorization for wholesale of medicines, the rest half were related to changes in already granted authorizations. During the inspections, 17 non-conformities (NCs) have been documented. The NCs were identified in 3 wholesalers and 6 deficiencies were classified as major. No critical deficiencies were found. NCs were found in 6.25% of the inspected companies. No critical NCs were identified and only 6 NCs were classified as major which demonstrated high level of compliance of distributions sites in Bulgaria with the requirements of GDP.